Working memory capacity modulates task performance but has little influence on task choice. - Butler, Karin; Arrington, Catherine; Weywadt, Christina (Memory & Cognition, 2011)
Variation in the ability to maintain internal goals while resolving competition from multiple information streams has been related to individual differences in working memory capacity (WMC). In a multitask environment, task choice and task performance are influenced by internal goals, prior behavior within the environment, and the availability of relevant and irrelevant information in the environment. Using the voluntary task-switching procedure, task performance, as measured by switch costs, was related to WMC, but only at short preparation intervals. Task choice processes were only weakly related to WMC. These findings are consistent with models of cognitive control that separate task choice processes from the processes of activating and maintaining task readiness. WMC is related to regulation of specific task parameters but not to choice processes integral to the coordination of multiple sources of information.